Energy, pollution, and economic development in Tunisia - Miniar Ben Ammar Sghari; Sami Hammami (Energy Reports, 2016)
Since the United Nations Conference on Environment and Development held its Rio meeting in 1992, where participants discussed the necessity of fighting against the hazardous effects of pollution and climate change, these issues have become even more pressing world-wide. The ever-increasing consumption of energy is depleting the planet's natural capital to a degree that could impact our future prosperity. According to the 2008 Living Planet Report, if demands for energy were to continue to grow at their current rates, by the mid-2030s we would need the equivalent of two planets to meet our global supply needs.11World Wildlife Federation (WWF), Living Planet Report 2008(Gland, Switzerland: WWF, 2008). The rising level of energy consumption that is occurring internationally also is being mirrored at regional and national levels. An interesting case study along these lines is Tunisia, which is one of the high-growth economies in the Middle East and North African area yet lacks sufficient energy supply to satisfy its growing demand. Tunisia looks like many nations around the world with a young population, growing economy, increasing domestic energy consumption, and the need to balance economic development with environmental concerns.
Keywords: 330; Economic development; Energy; Pollution; Relationship; Tunisia